Transforming Technology Towards Green Mobility: The Mediating Effect of Attitude on Consumers’Purchase Intention - A, Nowshath bee; M, Muthumeenakshi (International Journal of Accounting and Economics Studies, 2026)
As the world moves towards more sustainable transportation, electric two-wheelers are becoming viable alternatives to traditional vehicles, ‎particularly in developing nations. This research investigates the transforming technology towards green mobility factors influencing con-‎sumers' purchase intention with reference to the Vellore district, using Behavioural Science and Technology Adoption theories to identify ‎four key influencing factors: environmental concern, perceived economic benefits, social influence, and charging infrastructure. In this study, ‎a structured questionnaire was used and surveyed, in which 99 respondents were collected, and advanced statistical analysis (PLS-SEM) ‎was conducted. The study's results indicated that economic benefits and social influence had a significant impact on purchase intentions, ‎whereas environmental concerns and charging infrastructure had a minor effect on purchasing decisions. Nonetheless, charging infrastruc-‎ture influences consumer views towards electric scooters, even if those perceptions may not convert into actual purchase intentions. Accord-‎ing to the study's findings, economic benefits and social influences outweigh environmental motivations in consumer purchasing decisions ‎in the Vellore district. These findings are useful for governments, manufacturers, and marketers seeking to increase electric vehicle adoption, ‎as they suggest that efforts should be prioritized on economic incentives and infrastructure development over environmental benefits. In ‎addition, the study identifies prospective topics for further managerial and practical implementations of the findings.
Keywords: Consumer Attitude; Environmental Sustainability; Green Mobility; Green Technology; Transforming Technology; and Purchase Intention